Generation of circular prismatic dislocation loops in decahedral small particles. (15th March 2018) - Krauchanka, M.Yu.; Krasnitckii, S.A.; Gutkin, M.Yu.; Kolesnikova, A.L.; Romanov, A.E.; Aifantis, E.C.
Abstract: A theoretical model is proposed which describes stress relaxation in decahedral particles by generation of circular prismatic dislocation loops. Providing that the particle size exceeds a certain critical value, the nucleation of circular prismatic dislocation loops becomes an effective channel for residual stress relaxation in the particle. Under these circumstances, the loop expands until it reaches its optimal radius which increases with an increase of the particle radius. It is shown that both the critical particle radius and optimal loop radius strongly depend on the dislocation core energy, as well as on the material properties of the particle. Graphical abstract: Image 1